The impact of indoor environment quality (IEQ) on school children's overall comfort in the UK; a regression approach. (November 2020) - Korsavi, Sepideh Sadat; Montazami, Azadeh; Mumovic, Dejan
Abstract: Indoor Environment Quality (IEQ) is grouped into four main categories: thermal comfort, indoor air quality (IAQ), visual and acoustic comfort. Individual aspects of IEQ are investigated to examine their impact on children's overall comfort in primary schools in the UK. This study has surveyed 805 children in 32 naturally ventilated classrooms during non-heating and heating seasons. This study has calculated the proportion of comfort votes by individual aspects of IEQ, predicted comfort votes by multilinear regression model and estimated the probability of having uncomfortable votes by binary logistic regression. Results of this study highlight that the proportion of uncomfortable votes should be kept below 10%. The developed multilinear model suggests that for a unit change in Air Sensation Votes (ASVs) and operative temperatures (Top ), comfort votes change by 0.28 and 0.12, respectively. Developed multilinear and logistic regression models show that ASVs have a more significant impact on overall comfort than Top . To achieve acceptable comfortable votes and keep the probability of having uncomfortable votes below 10%, ASVs and Top should be kept within these limits: [ASV = very fresh and Top = 19–27 °C], [ASV = fresh and Top = 19–24 °C], and [ASV = OK and Top = 19–22 °C]. The ranges suggest that better perception of IAQ makes up for higher temperatures. It is advised to maintain individual aspects of IEQ, however, dissatisfaction with one aspect of IEQ does not necessarily result in overall discomfort unless that aspect is extremely unacceptable. Investigating the most influential factors on occupants' comfort suggests which building controls should be prioritized for designers. Highlights: The study evaluates comfort based on Indoor Environment Quality using regressions. Air quality and thermal environment are the most important aspects of comfort. Visual sensation has the least influence on overall comfort. Sensation votes have a higher impact on overall comfort than physical parameters. Dissatisfaction with one aspect of IEQ does not result in overall discomfort.